Perception of UHT Ready-to-Drink Coconut Water in Bangkok via Online Media - Songtham Mokanan; Phatchara Eamkijkarn Sabaijai (My University, 2023)
The objective of this research was to study the awareness of UHT coconut water in Bangkok via an online channel. Survey responses were collected from 404 participants (age range of 18 to 40 years old) who were exposed to online media and consumed UHT ready-to-drink coconut water. The data collected were then analyzed by descriptive statistical analysis for frequency, relative frequency, and standard deviation. The results showed that the group that has the highest awareness of online media is female (62.10%) at the age between 24 to 29 years old (48.00%), having bachelor's degrees (76.00%), and being employed in private companies (49.80%) with a salary range of 20,001-30,000 baht per month (30.90%). For the overall perception of UHT ready-to-drink coconut water, there is a high awareness from online media exposure of (x̄ = 3.84) and factors rank from high to low, i.e. Convenience (x̄ = 4.01), Communication (x̄ = 3.92), and worthiness (x̄ = 3.75), and consumers (Cost of Consumer) (x̄ = 3.69). respectively. It can be concluded that consumers order UHT ready-to-drink coconut water online due to its convenience.
Keywords: Salary; null